Hydrogen Supply Chain Optimisation with Green Electricity Generation for Energy Trading Between Industrial Parks - Muhammad Fakhri Salahuddin Ahmad Fadhil; Peng Yen Liew; Hazirah Hanim Zaharuddin; Angel Xin Yee Mah; Wai Shin Ho; Kok Sin Woon (Chemical Engineering Transactions)
Hydrogen can complement renewable energy to produce green electricity and green hydrogen. Most supply chain studies do not consider hydrogen demand in industrial zones and have never considered hydrogen as an energy source to meet industry's energy needs. This paper develops an optimal Hydrogen Supply Chain (HSC) network to minimise the overall cost of the energy system, considering the energy trading option across industrial zones. Grey and blue hydrogen are included with natural gas as the Steam Methane Reforming (SMR) plant feedstock and SMR with the Carbon Capture Storage (CCS) plant. Green electricity production from solar, wind, hydroenergy, and biomass gasification are considered to produce green hydrogen in this study. Through AIMMS modelling and optimisation, it was determined that the total daily cost (TDC) of the HSC network is 2,464 million USD/d. Hydrogen trading is essential to minimise the energy consumption of hydrogen production plants. Hydrogen trading is forcing one industrial zone with excess hydrogen to export to other industrial zones with insufficient hydrogen to meet its energy demand. In simple terms, hydrogen trading does not fully rely on hydrogen production plants but relies on transportation technology to import and export hydrogen for other industrial zones. With that, hydrogen trading can minimise the TDC of the HSC network and minimise the energy consumption from conventional hydrogen production plants. According to the results, the main exporter of hydrogen is industrial zone G2, with 115.57 t/d of hydrogen.